A comparison of visual and audio scaffolds in L2 English reading - Stephens, Meredith; Kaiser, Meagan Renee (Indonesian Journal of Applied Linguistics, 2018)
This is a study of Japanese learners’ perspectives on visual and audio scaffolds in the teaching of second language English reading. We compare the approaches of ER, according to Day Bamford’s (1998) ten principles (outlined below) in class, and Assisted Repeated Reading (ARR) of a work of fiction to a class. ARR refers to the reading aloud of a text multiple times to students as they follow along silently (see Taguchi Gorsuch, 2002). Two classes of students in required English classes undertook both ER and ARR. Both the ER and ARR enhanced the students’ comprehension of the texts; in the case of ER, most students chose picture books, which aided their comprehension. In the case of ARR, the embodied presence of the reader, and the modeling of prosody facilitated comprehension.